Aza[5]helicene Rivals N‐Annulated Perylene as π‐Linker of D−π−D Typed Hole‐Transporters for Perovskite Solar Cells. (19th May 2020) - Wang, Jianan; Shi, Huilei; Xu, Niansheng; Zhang, Jing; Yuan, Yi; Lei, Ming; Wang, Lidong; Wang, Peng
Abstract: The superior role of helical π‐linkers is demonstrated for the design of donor−π linker−donor typed molecular semiconductors in perovskite solar cells (PSCs). Flat N ‐annulated perylene (NP) and contorted aza[5]helicene (A5H) are side‐functionalized with methoxyphenyl and end‐capped with dimethoxydiphenylamine electron‐donor to afford two small‐molecule hole‐transporters J3 and J4. For methoxyphenyl functionalized π‐linkers, intermolecular π⋅⋅⋅π interactions in planar NP exist more extensively than those in helical A5H. However, for the dimethoxydiphenylamine derived hole‐transporters with high highest occupied molecular orbital energy levels, a part of the π⋅⋅⋅π interaction remains for J4 with A5H, while this desirable effect for charge transport is completely deprived for J3 with NP. Thus, the theoretically predicted hole mobility of J4 single‐crystal is even over two times higher than that of J3 one. Because of the larger size of the molecular aggregate, the hole mobility of the spin‐coated J4 thin film is also over three times as high as that of the J3 analog. Due to the reduced transport resistance and enhanced recombination resistance, PSCs with J4 exhibit a power conversion efficiency of 21.0% at standard air mass 1.5 global conditions, which is higher than that of 19.4% with J3 and that of 20.3% with spiro‐OMeTAD control. Abstract : The aza[5]helicene‐based hole‐transporter is superior to its congener with the planar N‐annulated perylene π‐linker. This study has highlighted that the use of a helical π‐linker for donor−π linker−donor typed organic semiconductors can retain stronger intermolecular π⋅⋅⋅π interactions and attenuated interface charge recombination, leading to better power conversion efficiency of perovskite solar cells.